Modern principles of public administration of pharmaceutical supply for the population in emergency situations - P. V. Olіynуk; B. P. Hromovyk (Zaporozhye State Medical University, 2015)
In conditions of the emergency situations' amount increasing the readiness of the state to provide affected people and all other segments of the population with full pharmaceutical provision is important. The aim of research is an analysis of the state of the legislative and regulatory framework of governmental administration by pharmaceutical provision of the population in the conditions of emergency situations. Materials and methods. We used methods of observation and synthesis, generalization and formalization, analysis of content. The object of the study were regulations, government pharmaceutical providing of population in emergency situations. Results. Studies show the need to develop methods and principles of public administration process to ensure people with pharmaceutical and specific methodological approaches in emergency situations. Conclusions. It has been established, that it is necessary to develop scientifically based methods of governance by the process of pharmaceutical providing the affected population.